2019
DOI: 10.3390/f10121126
|View full text |Cite
|
Sign up to set email alerts
|

Duration Limits on Field Storage in Closed Cardboard Boxes before Planting of Norway Spruce and Scots Pine Container Seedlings in Different Planting Seasons

Abstract: For spring plantings, conifer seedlings are usually packed in closed cardboard boxes and freezer stored over winter. Additionally, seedlings are increasingly being stored in cardboard boxes in spring, summer, and autumn plantings in Finland. The aim of this study was to determine the maximum safe duration for the field storage of Norway spruce (Picea abies (L.) Karst.) and Scots pine (Pinus sylvestris L.) container seedlings in closed cardboard boxes for different planting times (dates) in Nordic boreal condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In certain previous studies, small-sized Scots pine seedlings have also been observed to grow at least as well, and suffer less pine weevil damage, compared to larger-sized container seedlings [6,8,9]. However, they have been found to be more prone to storage and environmental stress factors, such as drought [8,[10][11][12]. To date, small-sized Scots pine seedlings have been used in forest regeneration mainly in the humid climate of the northern parts of Nordic countries.…”
Section: Introductionmentioning
confidence: 97%
“…In certain previous studies, small-sized Scots pine seedlings have also been observed to grow at least as well, and suffer less pine weevil damage, compared to larger-sized container seedlings [6,8,9]. However, they have been found to be more prone to storage and environmental stress factors, such as drought [8,[10][11][12]. To date, small-sized Scots pine seedlings have been used in forest regeneration mainly in the humid climate of the northern parts of Nordic countries.…”
Section: Introductionmentioning
confidence: 97%
“…The planting season for Norway spruce container seedlings in Nordic countries lasts from May to September (Luoranen et al 2019). Dormant, actively growing and short day treated Norway spruce (Picea abies (L.) Karst) seedlings are recommended to be planted in spring (May to mid-June), summer (June to late July) and autumn (August to September), respectively (Luoranen et al 2005(Luoranen et al , 2006(Luoranen et al , 2018Wallertz et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Finland, the average field storage duration of seedlings is two weeks overall during the planting season, varying from one to 49 days (Rantala et al 2003). Luoranen et al (2019Luoranen et al ( , 2020 recommend a field storage period of 1-2 weeks for dormant container seedlings, and two to four days for growing container seedlings. The recommended storage period for actively growing container seedlings is only a few days, because of their high susceptibility to drought stress (Grossnickle and Folk 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field storage in carboard boxes can significantly reduce the frost hardening and increase the seedling mortality [20]. Recent studies in Finland showed that the safe duration depends on the weather conditions and recommended only three days in summer and about a week in spring and early autumn [21].…”
Section: Introductionmentioning
confidence: 99%